(untitled) (The Educator Journal, 2025)
Nepal adopted a federal system of governance with the promulgation of its 2015 Constitution. While the implementation of federalism has been widely discussed in terms of ethnic identity, decentralization, and good governance, the role of geopolitical factors remains unexplored. Considering such a gap in research literature, this paper examines the influence of Nepal’s geopolitical realities on the implementation and stability of its federal structure. Employing a qualitative research method, the study draws on secondary sources such as books, policy documents, academic journals, newspapers, and relevant online resources. The findings reveal that Nepal’s federalism is significantly shaped by both internal and external geopolitical factors. Internally, demands for political representation and autonomy from various ethnic and regional groups, coupled with disputes over resource distribution and governance, have posed substantial challenges. Externally, Nepal’s strategic location between India and China has subjected it to competing influences from both powers, affecting economic policy, security, and the balance of power across government tiers. The study concludes that to sustain political stability and promote effective federal governance, Nepal must strategically manage its internal diversity and external geopolitical pressures Such strategies are inclusive governance, balanced diplomacy, maintaining equilibrium in relations with neighbours and the international community, security and preparedness.